Interactive art and visual communication design of AR-based selfie application - Zhang, Di; AlSagoff, Syed Agil; Yasin, Megat Al Imran; Muhammad Razi, Siti Aishah (Universidad Técnica de Manabí (UTM), 2022)
Augmented reality alludes in the utilization brand-new presentation innovation, sight and sound innovation, and human-computer communication innovation to make a computer overlay created virtual items, virtual scenes, or different framework into the prompts genuine scene, to accomplish incorporation with the general climate of the client. The client can outwardly believe that the simulated overlay is obtrusive data is a type of piece in the genuine climate in the vicinity of him. In accordance with the innovation of expanded reality and visual correspondence, this document \accomplishes the craftsmanship plan in the ongoing picture intelligent connection point of the promoting screen, carefully upgrades what is going on, enhances the visual feeling of the publicizing crowd, and transforms the commercial into an intuitive structure. This article examines the particular substance of the creation, illustrations, shading, extent, brilliance, and plan standards in the notice. We direct a poll overview and consolidate them as per the over 6 markers. Inquiry countless records for investigation, and lead a hypothetical examination of the continuous intelligent picture interface plan of the publicizing screen in light of increased reality innovation.